Your need doesn’t appeal to me: how social class shapes donation allocation preferences - Vieites, Yan Bernardes (2021)
When considering a charitable act, consumers must often decide on how to allocate their resources across a multitude of possible causes. Although existing research shows that social class influences charitable giving in general, it is unknown whether it systematically sways preferences for specific causes. This article assesses how the relative “urgency” of the causes under consideration (i.e., how critical to human survival the causes are) shapes the relationship between social class and prosociality. Across a series of studies in a highly unequal socioeconomic environment, we demonstrate that lower-class consumers prefer to donate to urgent causes (e.g., alleviating hunger) compared to non-urgent causes (e.g., encouraging cultural activities), whereas the effect reverses among higher-class consumers. Contrasting experiences with scarcity across social classes vary the consumers’ intrinsic sympathy toward people’s unmet basic needs, which in turn shapes donation allocation preferences. Consistent with this theoretical rationale, class differences in charitable allocations decrease when (a) vivid contextual cues induce sympathy among both higher- and lower-class consumers or (b) the experience with scarcity is similar across social classes.